Análise de rotas de fulga e saídas de emergências – estudo de caso na Câmara Municipal de Mossoró - Soares Segundo, Glênio Alves Diniz (Universidade Federal Rural do Semi-Árido, 2019)
The process by constructions becomes larger and smaller available areas, much cause of the great economic and social growth in which we are living, which requires a strong demand for buildings. In the same way that the growth of the buildings occurs, the number of fires of these buildings increases, which often occur in buildings built many decades and outside of the current legislation, due to the lack of inspection or even existing regulations at that time. The need arose for one of the oldest buildings in the city of Mossoró - Rn, where the municipal council is housed, in order to verify that the emergency exits are in accordance with current regulations, and if not, propose measures to solve the problem of having a safe building for its occupants. On-site visits were carried out, as well as a low floor analysis where it was possible to verify that the building did not take care of emergency exits, mainly in its stairs, proposing the construction of new stairs in addition to the expansion of some existing doors
Monografia
Keywords: Medidas Solucionarias; Norma Vigente; Edificação Antiga; Solving Measures; Current norm; Old Building; ENGENHARIAS::ENGENHARIA CIVIL